Public engagement professionals in a prestige economy: Ghosts in the machine. Issue 7 (3rd July 2022) - Watermeyer, Richard; Rowe, Gene
ABSTRACT: Over the last decade, there has been significant investment made by the UK higher education policy and funding community in embedding public engagement within British universities. While some public engagement is undertaken by university staff – often on a voluntary and unpaid basis – much is carried out by public engagement professionals (PEPs), typically from within professional services divisions. The following account, based upon a multi-site case study of institutional leadership for public engagement, adopts a Bourdieusian lens to consider the challenges faced by PEPs as 'non-academics' working within the UK's university sector as a prestige economy. It reveals their struggle to gain a professional parity of esteem with academics, and how the discrediting of their expertise by the latter forms a challenge to their leadership and thus their displacement within universities as highly stratified organisations. Ergo, we find the evanescing of public engagement as a formal institutional commitment. 2018 2011 )t.